2018
DOI: 10.1016/j.msea.2018.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characteristics of Portevin-Le Chatelier effect in Ti-Mo alloys under thermo-mechanical loading

Abstract: The Portevin-Le Chaterlier (PLC) effect in Ti-12Mo and Ti-15Mo alloys has been investigated by using uniaxial tensile tests in a temperature range of 25-350 ℃ with an applied strain rate of the order of 10 -3 s -1 , coupled with a digital image correlation (DIC) method. The experimental results show an increase of the yield stress from 25°C to 250°C followed by a decrease. Moreover, PLC effect occurs above 250°C and stress drop magnitude increases while the number of stress drops per unit time decreases with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Most models explaining Portevin-Le Chatelier (PLC) effects are based on the assumption that discontinuous deformation is the result of dynamic strain aging caused by the interaction between mobile dislocations and diffusing impurity atoms [21]. In addition to the typical mechanisms based on the interaction of dislocations and impurity atoms, there are many other interpretations of the PLC effect [22]. In particular, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Most models explaining Portevin-Le Chatelier (PLC) effects are based on the assumption that discontinuous deformation is the result of dynamic strain aging caused by the interaction between mobile dislocations and diffusing impurity atoms [21]. In addition to the typical mechanisms based on the interaction of dislocations and impurity atoms, there are many other interpretations of the PLC effect [22]. In particular, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al [9] investigated the PLC effect and the band formation in titanium alloys Ti-12Mo and Ti-15Mo under the uniaxial tension, at 0.001 s -1 strain rate and within 25-350 °С temperature range. It was found that the amplitude of the strain drops positively correlated with the temperature and negatively correlated with deformation and the molybdenum content, while the number of the strain drops showed an opposite tendency.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the microstructure of water-quenched tensile samples is analyzed by optical micrographs (OM) and X ray diffraction (XRD) with Cu Kα1 radiation (λ = 0.154060 nm) using a Philips PW3710 diffractometer. Note that the details of OM sample preparation processes are described by Luo et al [69]. Figs.…”
Section: Introductionmentioning
confidence: 99%
“…4(d) that type C bands appear at random intervals along the gauge length in Ti-10Mo alloy for the experimental condition (350 °C & 10 -4 s -1 ). In general, the type of PLC bands is related to the spatial coupling force [69]. Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation